2009
DOI: 10.14238/pi49.6.2009.349-54
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between cord blood bilirubin level and incidence of hyperbilirubinemia in term newborns

Abstract: Background Discharging healthy term newborns from thehospital after delivery at increasingly earlier postnatal ages hasrecently become a common practice due to medical, social, andeconomic reasons, however it contributes to readmission becauseof jaundice.Objective To investigate the correlation between level of cordblood bilirubin and development of hyperbilirubinemia amonghealthy term newborns.Methods Prospective observational study was performed on88 healthy term newborns. Cord blood was collected for thetot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
15
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 0 publications
9
15
2
1
Order By: Relevance
“…The mean total cord bilirubin at birth and TCB at 72 hours of age, had no statistically significant relation to gender and the type of delivery, and consistent with the results of some studies (10,15,17,18). Two studies (19,20) found that UCSB level was significantly different between the sexes. We assume that the difference may be the result of G6PD enzyme deficiency among males as it is an X-linked recessive disorder that was excluded from our study, and they did not exclude these types of babies.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The mean total cord bilirubin at birth and TCB at 72 hours of age, had no statistically significant relation to gender and the type of delivery, and consistent with the results of some studies (10,15,17,18). Two studies (19,20) found that UCSB level was significantly different between the sexes. We assume that the difference may be the result of G6PD enzyme deficiency among males as it is an X-linked recessive disorder that was excluded from our study, and they did not exclude these types of babies.…”
Section: Discussionsupporting
confidence: 86%
“…25 mg/dL, this is in line with other studies(6,15). Satrya et al(19) showed that UCSB level > 2.54 had high specificity and sensitivity. Zeitoun et al(15) also found that UCSB level > 2.15 mg/dL had the highest sensitivity and at this critical cord bilirubin level, negative predictive value was very high.…”
supporting
confidence: 87%
“…However, studies done by Satrya and Maisels and Kring had showed that male babies are at a higher risk of developing icterus and subsequent intervention for icterus. 11,12 But the presentation study is in correlation with study done by Taksande et al which states that there is no relation between neonatal hyperbilirubinemia and the sex of the baby. 5 In this study, it was noted that the gestational age at which the baby was born had a positive correlation with the presence lower albumin levels.…”
Section: Figure 1: Association Between Cord Albumin Level and Neonatamentioning
confidence: 50%
“…Neonates with serum bilirubin <2mg/dl have low risk for neonatal hyperbilirubinemia, thus can be kept in low priority as compared to neonates with cord blood serum bilirubin >3mg/dl. Neonates with Cord Blood Bilirubin level ≥3mg/dl should be followed more frequently to reduce morbidity and mortality due to neonatal hyperbilirubinemia [13][14][15][16].…”
Section: Resultsmentioning
confidence: 99%